Роль і значення актів місцевого самоврядування в системі правових актів України - Кравчук, Володимир Миколайович; Kravchuk, Volodymyr M. (Тернопільська академія народного господарства ; Юридичний інститут, 2001)
The article reveals the role and significance of the acts of local government in the system of the legal acts of Ukraine. It points out the importance of local government for the formation of civic society, democratic state, analyzes the legal grounds for the local government in Ukraine. The article also deals with the notion of the acts of local government at the basis of the definitions of the law-scholars.